Aplikasi Bakteri Probiotik untuk Meningkatkan Mutu Fisiologi dan Kesehatan Bibit Cabai (Capsicum annuum L.) - Tefa, Anna; Widajati, Eny; Syukur, Muhamad; Giyanto, dan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTThe use of probiotic bacteria as biocontrol agents is one of the methods of controlling anthracnose disease caused by Colletotrichum acutatum. The objective of this research was to suppress the infection of C. acutatum and increase chilli pepper seedling vigour. The research involved factorial experiments arranged in a completely randomized design with two factors. The first factor was seed coating involving six treatments, i.e., control, seed coating without bacteria, seed coating with Bacillus sp., Pseudomonas sp., Actinomycetes sp, and fungicide. The second factor was the seed storage period where six storage periods were experimented, i.e., 0, 1, 2, 3, 4, 5, and 6 months. The results showed that the coating treatment of Bacillus sp., Pseudomonas sp., and Actinomycetes sp. improved germination, growth rate and number of leaves and reduced the incidence of attacks and infection of hypocotyls at 5 month storage period.Keywords: Actinomycetes sp., Bacillus sp., Pseudomonas sp., seed coating, storage period